Exogenous Cortisol Administration; Effects on Risk Taking Behavior, Exercise Performance, and Physiological and Neurophysiological Responses - Robertson, Caroline V.; Immink, Maarten A.; Marino, Frank E. (Frontiers in Physiology, 2016)
Rationale Exogenous cortisol is a modulator of behaviour related to increased motivated decision making (Putman et al., 2010), where risky choices yield potentially big reward. Making risk based judgements has been shown to be important to athletes in optimising pacing during endurance events (Renfree et al., 2014; Micklewright et al., 2015). Objectives Therefore, the aims of this study were to examine the effect of 50mg exogenous cortisol on neurophysiological responses and risk taking behaviour in 10 healthy men. Further to this, to examine the effect of exogenous cortisol on exercise performance. Methods Cerebral responses at rest and during exercise were measured in 10 male cyclists, when exogenous cortisol was provided. Following one hour of resting measures, risk taking behaviour was assessed, after which a 30 min cycling time trial was undertaken. Results Cortisol increased risk taking behaviour from baseline testing. This was in line with significant neurophysiological changes at rest and during exercise. Exercise performance however, was not significantly changed. Conclusion These results are in line with previous research showing altered risk taking behaviour following exogenous cortisol, however the altered behaviour did not translate into changes in exercise performance.